2016
DOI: 10.1007/s00330-016-4488-y
|View full text |Cite
|
Sign up to set email alerts
|

Liver and biliary damages following transarterial chemoembolization of hepatocellular carcinoma: comparison between drug-eluting beads and lipiodol emulsion

Abstract: • DEB-TACE demonstrated more therapy-related hepatic locoregional complications compared to cTACE. • TACE-related hepatic locoregional toxicities occurred more frequently with high baseline PT value. • cTACE may be more appropriate in patients with high baseline PT value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 33 publications
6
62
2
Order By: Relevance
“…Thus, an auspicious impact on OS in treatment of NELM disease was also expected [14, 3235]. Yet, initial outcome reports for DEB-TACE in patients with NELM were disappointing, and in some cases significant toxicities, such as a higher incidence of biliary injury, occurred which required a modification of protocol [36, 37]. As reported previously, the MOS for patients after receiving cTACE can range from 24 to 44 months [27, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an auspicious impact on OS in treatment of NELM disease was also expected [14, 3235]. Yet, initial outcome reports for DEB-TACE in patients with NELM were disappointing, and in some cases significant toxicities, such as a higher incidence of biliary injury, occurred which required a modification of protocol [36, 37]. As reported previously, the MOS for patients after receiving cTACE can range from 24 to 44 months [27, 38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DEB‐TACE is associated with significantly more biliary injuries than c‐TACE . However, to our knowledge, there have been no reports of hemobilia immediately after DEB‐TACE for HCC with intrahepatic bile duct invasion.…”
Section: Discussionmentioning
confidence: 84%
“…Among 16 articles that retrospectively analyzed DEB‐TACE versus cTACE, five described the superiority of DEB‐TACE, three showed an advantage of cTACE, and the remaining eight showed equivalent effect or adverse events. Individual evaluation of objective response rate, TTP, OS, and adverse events, did not show definite advantages of DEB‐TACE over cTACE in these retrospective studies.…”
Section: Transcatheter Arterial Therapymentioning
confidence: 99%